2020
DOI: 10.7717/peerj.9413
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood caries and its associations with sugar consumption, overweight and exclusive breastfeeding in low, middle and high-income countries: an ecological study

Abstract: Aim This ecological study examined the associations between the prevalence of early childhood caries (ECC), overweight, country’s per capita sugar consumption and duration of exclusive breastfeeding. Methods Per capita consumption of sugar in kilograms, percentage of children exclusively breastfed until 6 months of age, percentage of 0–5-year-old children with overweight status, and percentage of 3–5-year-old children with ECC were compared among low-income countries (LICs), middle-income countries (MICs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…These findings corroborated previous similar studies carried out among Nigerian children [5][6][7][8]. A recent study reported that despite the lower consumption of sugar among children from low-income countries, the prevalence of ECC was high, this could possibly be explained by the impact of the frequency of consumption when compared to the quantity of consumption of sugar [31]. Also, there is access to cheaper high sugar containing meals in low-resourced settings which is a readily accessible alternative diet [32].…”
Section: Discussionsupporting
confidence: 92%
“…These findings corroborated previous similar studies carried out among Nigerian children [5][6][7][8]. A recent study reported that despite the lower consumption of sugar among children from low-income countries, the prevalence of ECC was high, this could possibly be explained by the impact of the frequency of consumption when compared to the quantity of consumption of sugar [31]. Also, there is access to cheaper high sugar containing meals in low-resourced settings which is a readily accessible alternative diet [32].…”
Section: Discussionsupporting
confidence: 92%
“…According to the growing body of literature, the increasing ECC rate is associated with higher sugar intake [ 44 ]. In a worldwide ecological study, the per capita added sugar consumption in low-, middle-, and high-income countries was assessed.…”
Section: Discussionmentioning
confidence: 99%
“…The added sugar consumption in low-income countries was found to be significantly lower than in middle- and high-income countries. However, this study found a correlation between the prevalence of ECC and sugar consumption only in middle-income countries [ 44 ]. The multivariate analysis revealed that the contribution of sugar consumption at population level has a significant impact on YLD, which suggests that YLD could be improved by lowering sugar consumption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations